Sex chromosomes/hormones and the tumor microenvironment of non-reproductive cancers - Zhang, Chun-Miao; Ge, Zhong-Bo; Zhou, Hai-Hong; Wei, Meng-Xiao; Ding, Xin-Yuan; Lin, Zhe-Zheng; Wang, Ming-Yu; Bai, Cai-Juan (Frontiers in Immunology, 2025)
Cancer exhibits profound sexual dimorphism in incidence and therapeutic outcomes, driven by the interplay between biological sex determinants and immune regulation. Besides established environmental risk factors (e.g., male-predominant smoking/alcohol consumption), emerging evidence identifies the tumor immune microenvironment (TIME) as a pivotal mediator of sex disparities in carcinogenesis and immunotherapy response. This review synthesizes recent advances in two fundamental mechanisms: (1) Sex chromosome biology: Recent studies delineate the Ubiquitous loss of chromosome Y (LOY) of male cancers that promotes immunosuppressive TIME remodeling, while X-chromosome inactivation escape in females enhances antitumor immunity; (2) Endocrine regulation: Androgen receptor signaling induces T-cell exhaustion via PD-1 transcriptional activation in males. Estrogen-ERα boosts cancer progression via PD-L1 high expression, whereas ERβ inhibits cancer progression via CD8+ T cell activation in females. This mechanistic synthesis provides actionable strategies for precision immuno-oncology trials targeting sex-based immunological divergence.